STUDI PEMETAAN SOSIAL TERHADAP PENGEMBANGAN MASYARAKAT SEKTOR PENDIDIKAN DI DESA LINGKAR TAMBANG KABUPATEN BOLAANG MONGONDOW - Hamdi Gugule; Romi Mesra (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2022)
The purpose of this social mapping study is to find and obtain comprehensive information and data regarding the condition of Community Development in the education sector in the villages surrounding the mine, Bolaang Mongondow Regency. The research method is descriptive quantitative by combining narrative and calculation. The results showed that for the community around the mine there were problems related to the availability of learning facilities and infrastructure. The average school in the study area of ​​social mapping still lacks teachers, so each school recruits honorary staff who are still educated at the same high school level and are continuing their undergraduate education at the Open University for the Primary School Teacher Education Study program. Also APK and APM in the villages around the mine there are still school-age children who are not in school. It is hoped that the research can be input for the government and the community as well as the mining industry in advancing the education sector in rural areas.